2001
DOI: 10.1055/s-2001-12805
|View full text |Cite
|
Sign up to set email alerts
|

New Endoscopic Treatment for Intramucosal Gastric Tumors Using an Insulated-Tip Diathermic Knife

Abstract: Compared with conventional EMR, this new method may have significant benefits, particularly regarding one-piece resection of lesions between 11 and 20 mm in size, and may also have a lower recurrence rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
260
3
5

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 385 publications
(278 citation statements)
references
References 3 publications
4
260
3
5
Order By: Relevance
“…Although the IT-ESD technique is complicated, it might be worth trying as the first therapy for mucosal gastric carcinoma because of its high one-piece resection rate (1,2). The introduction of our treatment protocol did not affect the operation time of IT-ESD.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Although the IT-ESD technique is complicated, it might be worth trying as the first therapy for mucosal gastric carcinoma because of its high one-piece resection rate (1,2). The introduction of our treatment protocol did not affect the operation time of IT-ESD.…”
Section: Discussionmentioning
confidence: 91%
“…The reported incidence of bleeding in IT-ESD was higher than in EMR using conventional methods. Ohkuwa et al (1) reported that the incidence of bleeding in IT-ESD was as high as 22%. In our study, the bleeding frequency was higher than Ohkuwa et al (1) reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite this limitation, our study provides information and identifies the potential complications associated with ESD. Compared to Hosokawa's original description [11], our ESD procedure involves several slight modifications that, in our opinion, make it easier to perform. We considered a complete resection of GIST to have occurred when severe histological criteria were respected (en bloc resection; entire capsule preserved and normal tissue visible at the deepest margin of the lesion).…”
Section: Discussionmentioning
confidence: 99%
“…ESD according to Hosokawa et al [11] was performed as follows: SMTs with a degree of elevation [50 % and with an acute angle with respect to the underlying mucosa were endoscopically treated through a hemicircumferential incision around the lesion. For tumors of low elevation and at an obtuse angle with respect to the underlying mucosa, a complete circumferential incision was performed to make easier the spontaneous spillage of the lesions from the deeper layer of the gastric wall (Fig.…”
Section: Endoscopic Proceduresmentioning
confidence: 99%